Pengembangan Produk Jasa Perbankan Syariah : Tinjauan Dari Perspektif Maqasid Syariah - Dwi Khairunnisa; Sarah Padillah (Pusat Riset dan Inovasi Nasional, 2025)
Shariah banking has developed rapidly over the past few decades, but the development of shariah banking services is still not optimal. This article aims to analyze the development of shariah banking services from the perspective of Maqasid Syariah. The research findings indicate that the development of shariah banking services must be based on the principles of Maqasid Syariah, namely protecting religion, life, intellect, progeny, and wealth. This article also finds that shariah banking services that meet the principles of Maqasid Syariah can increase public trust in shariah banking and improve community welfare.. Therefore, shariah banks must develop more innovative services that meet community needs based on the principles of Maqasid Syariah.